Strategic analysis of a water rights conflict in the south western United States. (15th September 2016) - Philpot, Simone; Hipel, Keith; Johnson, Peter
Abstract: A strategic analysis of the ongoing conflict between Nevada and Utah, over groundwater allocation at Snake Valley, is carried out in order to investigate ways on how to resolve this dispute. More specifically, the Graph Model for Conflict Resolution is employed to formally model and analyze this conflict using the decision support system called GMCR+. The conflict analysis findings indicate that the dispute is enduring because of a lack of incentive and opportunity for any party to move beyond the present circumstances. Continued negotiations are not likely to resolve this conflict. A substantial change in the preferences or options of the disputants, or new governance tools will be required to move this conflict forward. This may hold lessons for future groundwater conflicts. It is, however, increasingly likely that the parties will require a third party intervention, such as equal apportionment by the US Supreme Court. Highlights: We model a water allocation dispute over an aquifer underlying the Nevada-Utah border. The Graph Model for Conflict Resolution is used to model and analyze the conflict. The dispute is strategically analyzed to gain insights into the enduring quality and likely outcomes of the conflict. This conflict is not likely to be resolved by continued negotiation. This conflict is likely to result in equitable apportionment by the Supreme Court.